Youth transitions, international student mobility and spatial reflexivity being mobile? - Cairns, David (Palgrave Macmillan, 2014)
"International Student Mobility is vital to the future of Europe: the circulation of tertiary-educated youth between Member States represents a means through which the European Union can avoid a massive wastage of talent and, simultaneously, enable its skilled and qualified young people to make the best of their abilities. This book explores this topic in three contemporary European contexts: Portugal, the Republic of Ireland and the United Kingdom. A critique of existing theoretical perspectives on student mobility leads to the introduction of the concept of spatial reflexivity, denoting the process through which mobility plans are formulated among those making the transition to adulthood. However, while the findings from the three studies indicate that there is a huge level of interest in the idea of moving abroad for the next educational or occupational step actual prospects for being mobile appear more restricted, often leaving mobility tantalizingly out of reach. This disparity is explained by a range of factors, including the impact of the global financial crisis and the importance of family and social networks in encouraging and inhibiting transnational movement, in addition to insufficient policy recognition of the mobility needs of tertiary-educated youth outside the main metropolitan centres of Europe"--
Machine generated contents note: -- 1. Introduction2. Mobile Being3. Becoming Mobile4. The Mobility Promise5. A Mobile Future?
Keywords: Student mobility / Europe; Youth / Europe; Residential mobility / Europe; Youth / Europe / Attitudes; EDUCATION / Higher; EDUCATION / Students & Student Life; POLITICAL SCIENCE / Globalization; SOCIAL SCIENCE / Emigration & Immigration; SOCIAL SCIENCE / Human Geography; Globalisierung; Jugend; Migration; Auslandsstudium; Studentenaustausch; Soziale Mobilität; Europe / Emigration and immigration; Europa; Tschechoslowakei; Irland; Portugal; Großbritannien